Electric Buses : Why Now? - Graham, John (International Finance Corporation, Washington, DC, 2020)
There is a quiet revolution underway in a previously sleepy segment of the transport sector: the electrification of municipal buses and other intra-city vehicles. As McKinsey reported last October, the compound annual growth rate of battery-electric buses has exceeded 100 percent since 2013- surpassing that of every other electric vehicle segment. Investing in battery-electric buses - as well as other high-use vehicles, such as e-delivery trucks - is an effective way for International Finance Corporation (IFC) to move the needle on air quality and greenhouse emissions from urban transportation. The opportunity is massive, and IFC has the capacity to fast-track implementation. It’s time to hit the accelerator. A cocktail of technology, investment, and scale in electric buses (and other high-use intra-city electric vehicles) will soon reach a point where reliability and cost advantages create the death spiral for internal combustion engines. Superior technology and declining costs will eventually overwhelm the old, static, diesel driven transportation paradigm.